The Effects of Resuscitative Fluid Therapy on the Endothelial Surface Layer - Smart, Lisa; Hughes, Dez (Frontiers in Veterinary Science, 2021)
The goal of resuscitative fluid therapy is to rapidly expand circulating blood volume in order to restore tissue perfusion. Although this therapy often serves to improve macrohemodynamic parameters, it can be associated with adverse effects on the microcirculation and endothelium. The endothelial surface layer (ESL) provides a protective barrier over the endothelium and is important for regulating transvascular fluid movement, vasomotor tone, coagulation and inflammation. Shedding or thinning of the ESL can promote interstitial edema and inflammation and may cause microcirculatory dysfunction. The pathophysiologic perturbations of critical illness and rapid, large-volume fluid therapy both cause shedding or thinning of the ESL. Research suggests that restricting the volume of crystalloid, or ‘clear’ fluid, may preserve some ESL integrity and improve outcome based on animal experimental models and preliminary clinical trials in people. This narrative review critically evaluates the evidence for the detrimental effects of resuscitative fluid therapy on the ESL and provides suggestions for future research directions in this field.